Effectiveness of reduced doses of flumioxazin herbicide at weed control in direct sow onions - Melo, Christiane Augusta Diniz; Barbosa, Amanda Rocha; Dias, Roque de Carvalho; Silva, Gustavo Soares da; Reis, Marcelo Rodrigues dos (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2019)
The recommended application of most herbicides in onion crops is after transplanting seedlings with four true leaves. In the direct sowing system, this recommendation is considered late; an alternative management is the application of reduced doses starting with a true leaf. The objective of this study was to evaluate the use of reduced doses of flumioxazin in the early phenological stages of onions on bulb yield. Two field experiments were installed, and five doses of flumioxazin (5, 10, 15, 20, and 25 g ha-1) were applied in three phenological stages (1st, 2nd, and 1st+3rd true leaf); weed control was carried out. The results demonstrated the efficacy of reduced doses of flumioxazin on onion crop in the early stages. The dose of 20 g ha-1 showed use potential in the two experiments for the cvs. Perfecta and Sirius, enabling reductions of 77 to 88% of the commercial dose recommended for onions established with seedling transplanting. The application of flumioxazin in the 2nd leaf reduced commercial productivity and was ineffective in the control of weeds. The application in the 1st + 3rd leaf, despite being an effective control, caused greater phytotoxicity and, therefore, reduced commercial productivity. The best strategy for weed management is 20 g ha-1 flumioxazin applied to onion plants when they reach the true first leaf stage.